(untitled) (Journal of Science & Technology, 2021)
The human intestinal microbiota evolves from an immature and unstable ecosystem during infancy into a more complex and stable ecosystem in adulthood. Diet is one of the main factors contributing to the composition and diversity of the human intestinal microbiota. From birth, breast milk offers the best nutritional regime for maturation of the gut, whereas the introduction of solid food selects the most adapted bacteria, converging towards an adult-like microbiota. The gut microbiota plays an important role in host health, influencing the maturation of the immune system and regulating energy metabolism. Moreover, it has become evident that the microbiota can affect brain function and behaviour. On this bidirectional communication between intestine and the central nervous system (CNS), the so-called gut-brain axis, the gut influences brain development and biochemistry, whereas the brain affects gastrointestinal function. In this context, probiotics and prebiotics have been used as dietary strategies aimed at improving host health by modulating the gut ecosystem and, consequently, affecting host stress-responses, behaviour, and cognition.